Real-time selective monitoring of allergenic Aspergillus molds using pentameric antibody-immobilized single-walled carbon nanotube-field effect transistors1. Issue 20 (6th March 2015) - Jin, Joon-Hyung; Kim, Junhyup; Jeon, Taejin; Shin, Su-Kyoung; Sohn, Jong-Ryeul; Yi, Hana; Lee, Byung Yang
<x xml:space="preserve">Abstract</x> A SWNT-FET directly functionalized with immunoglobulin M shows a wide detection range from sub-picomolar to micromolar with an excellent sensitivity due to chemical gating in selective monitoring of fungal allergens.